FENOMENA MASYARAKAT MENTAWAI MASIH MEMPERTAHANKAN AGAMA BAHA’I (Studi Kasus Desa Mongan Poula Kecamatan Siberut Utara Kabupaten Kepulauan Mentawai) - nita veronika; nilda elfemi; yuhelna yuhelna (STKIP PGRI Sumatera Barat, 2021)
This researtch is motivated by the factors that cause the Mentawai, people of Mongan Poula village, norh Siberut district, to still maintain materials because Baha’i is an indenpenden and universal religion. where it focuses on the unity of mankind, this research aims to (1) describe the spread of the Baha’i religion in Mentawai so that is still maintained among the community, (2) describe the factors that cause Mentawai society still maintain the Baha’i religion.The theory used in this study is a phenomenological theory according to Alfret Schutz. this research method is a qualitative approach method, in the form of descriptive where qualitative research is study that analizes the proces of a social phenomenom and a study that analizes what is behid the information data, by using collection techniques. the data in this study are documents. observation and interviews, data analysis through the stages of data collection, data presentation and conclusions drawing.The results of this study are (1) an overview of Baha’i beliefs in the village of Mongan Poula, (2) the spread of the Baha’i religion in Mentawai, (3) the factors that cause the Mentawai community to still maintain the Baha’i religion, which includes (a) the Baha’i religion is universal, (b) belives that there is only one god,(c) the teaching recognizes that mankind is one.KeyWords: Phenomenom, Society, Baha’i